Feasibility and efficacy data from a ketogenic diet intervention in Alzheimer's disease - Taylor, Matthew K.; Sullivan, Debra K.; Mahnken, Jonathan D.; Burns, Jeffrey M.; Swerdlow, Russell H. (Alzheimer's & dementia : translational research & clinical interventions, 2018)
We assessed the feasibility and cognitive effects of a ketogenic diet (KD) in participants with Alzheimer's disease. The Ketogenic Diet Retention and Feasibility Trial featured a 3-month, medium-chain triglyceride–supplemented KD followed by a 1-month washout in clinical dementia rating (CDR) 0.5, 1, and 2 participants. We obtained urine acetoacetate, serum β-hydroxybutyrate, food record, and safety data. We administered the Alzheimer's Disease Assessment Scale-cognitive subscale and Mini–Mental State Examination before the KD, and following the intervention and washout. We enrolled seven CDR 0.5, four CDR 1, and four CDR 2 participants. One CDR 0.5 and all CDR 2 participants withdrew citing caregiver burden. The 10 completers achieved ketosis. Most adverse events were medium-chain triglyceride–related. Among the completers, the mean of the Alzheimer's Disease Assessment Scale-cognitive subscale score improved by 4.1 points during the diet (P = .02) and reverted to baseline after the washout. This pilot trial justifies KD studies in mild Alzheimer's disease. •The medium-chain triglyceride–supplemented KD was feasible in very mild (clinical dementia rating [CDR] 0.5) and mild (CDR 1) Alzheimer's disease participants, as 10 of 11 participants adhered to the dietary protocol.•The medium chain triglyceride-supplemented KD was not feasible in moderate (CDR 2) Alzheimer's disease participants as all four of these participants withdrew from the study.•Dietary compliant participants had a 4.1-point mean improvement on Alzheimer's Disease Assessment Scale-cognitive subscale scores from baseline to the end of the diet. Alzheimer's Disease Assessment Scale-cognitive subscale improvements diminished after a 1-month diet washout period.